Contractors and Naval Policy. The Victualling of the Spanish Navy in the Beginning of the War against Great Britain, 1739-1741 - María BAUDOT MONROY (Studia Historica: Historia Moderna, 2014)
In 1739 while British and Spanish diplomats tried to avoid a war, both nations prepared the infrastructure to arm their respective Navies. The mobilization of the Spanish resources for war was very much hampered by the bankruptcy of March that same year. While for Britain the victualling of the fleet was a challenge, for Spain the need to ensure the supply of food conditioned the political and financial decisions and increased the contractors privileges as well as the dependency for their services of the crown.